Design and Development of 20 channels shaping amplifiers and discriminators using Eagle. - d. N Haque Mia, M S Alam2, Mahmudul Hasa, M. Nazrul Islam, T. Fujiwara1, S. Kenji1 Kh. Asaduzzaman, Md. Shahzamal, (International Journal of Scientific Research and Management (IJSRM), 2013)
A study on 20 channels consisting of shaping amplifiers and discriminators has been described in this paper. This module has been designed, fabricated and tested using CAD tool EAGLE .A comprehensive study of the module like basic constituent, operating principle, mathematical derivation and testing results have been presented. The board has been designed with SMD components with 1μs shaping time constant and an integral discriminator of few mV to supply span (5V). Therefore, the simplest concept for pulse shaping is proposed that was used of a CR high-pass filter followed by an RC low-pass filter. Thereafter, 100% finished 2-layer board has been created by Autorouter with desired track size and layer. Finally, adding the ground and mounting holes manufacturing data have been created by using CAM processor and sent to board house for fabrication. After fabrication, the board has been assembled and tested successfully